Viability Test and Polyethylene Glycol (PEG) Soaking Factor of Soybean Seeds Due to Shading Stress - Deddy Wahyudin Purba; Suswati Suswati; Zoelhery Noer; Fanisa Dwi Adisty (Universitas Labuhanbatu, 2024)
Soybeans are a type of agricultural crop commodity in Indonesia that has benefits for society, especially as a source of vegetable protein. The aim of this research is to measure the viability test of soybean seeds and the soaking factor of polyethylene glycol due to shade stress. The research was carried out in the Tissue Culture Laboratory at Asahan University from December 2023 to January 2024. The researchers used a completely randomized factorial design (CRD) with 2 factors: first, soybean variety due to shade stress consisting of four levels, including V1 = Dena 1, V2 = Dena 2 , V3 = Denasa 1 and V4 = Denasa-2. The second factor is the duration of soaking in polyethylene glycol with a concentration of 7.5% consisting of four levels (P0) (control), (P1) 3 hours, (P2) 5 hours, (P3) 7 hours. Observed variables consist of maximum growth potential, germination capacity (%), growth simultaneity (%) and vigor index. Research data was analyzed using variance analysis procedures to determine whether there was an effect of each treatment. The soybean seed variety treatment was effective on the maximum growth potential of the Dena-1 V1 variety (96.67%), germination capacity (57.08%), growth simultaneity (59.17%) and vigor index (70.83%). The long soaking treatment of Polyethylen Glycol (PEG) had no significant effect on maximum growth potential, germination capacity and vigor index. but the real influence on the simultaneity of growth with results is P2 (5 hours) 44.17%. There is no interaction various seed varieties and the length of soaking in Polyethylen Glycol (PEG)